THE EFFECT OF GOVERNMENT EDUCATION SPENDING ON ECONOMIC GROWTH THROUGH SCHOOL ENROLLMENT IN INDONESIA - Lestari, Nur Indah (Polytechnic of State Finance STAN, 2016)
This paper examines the effect of government spending on education on growth as an indirect process through enrollment rate, specifically in Indonesia. Using a panel data set of 26 provinces from 2000 to 2010 and applying fixed effect approach of panel regression, we find that government spending on education has a positive relationship with enrollment with one-year lag; also, the data show that enrollment affect growth significantly. By enacting the chain rule, government spending on education has a positive effect in economic growth indirectly. Together, these findings suggest that raise government spending on education can increase enrollment rate and enhance economic growth.Â